2019
DOI: 10.1016/j.str.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the PKA RIα Holoenzyme with the FLHCC Driver J-PKAcα or Wild-Type PKAcα

Abstract: Fibrolamellar hepatocellular carcinoma (FLHCC) is driven by J-PKAca, a kinase fusion chimera of the J domain of DnaJB1 with PKAca, the catalytic subunit of protein kinase A (PKA). Here we report the crystal structures of the chimeric fusion RIa 2 :J-PKAca 2 holoenzyme formed by J-PKAca and the PKA regulatory (R) subunit RIa, and the wild-type (WT) RIa 2 : PKAca 2 holoenzyme. The chimeric and WT RIa holoenzymes have quaternary structures different from the previously solved WT RIb and RIIb holoenzymes. The WT R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…Second is the cross communication between the CNB-B domain with the J-Domain, which is revealed in the cryo-EM structure. As seen in previous structures, the J-domain is very flexible [11,2]; however, in the RIIβ holoenzyme, we see that the flexibility of the J-domain also appear to influence the dynamic features of its adjacent CNB-B domain as well as the A-helix that it is fused to. The J-domain can also further influence the dynamic features of the CNB-B domains in the RIIβ holoenzyme, which we did not see in the RIα holoenzyme.…”
Section: Structure and Dynamics Of Wt And Dnajb1-pkac Riiβ Holoenzymessupporting
confidence: 78%
See 2 more Smart Citations
“…Second is the cross communication between the CNB-B domain with the J-Domain, which is revealed in the cryo-EM structure. As seen in previous structures, the J-domain is very flexible [11,2]; however, in the RIIβ holoenzyme, we see that the flexibility of the J-domain also appear to influence the dynamic features of its adjacent CNB-B domain as well as the A-helix that it is fused to. The J-domain can also further influence the dynamic features of the CNB-B domains in the RIIβ holoenzyme, which we did not see in the RIα holoenzyme.…”
Section: Structure and Dynamics Of Wt And Dnajb1-pkac Riiβ Holoenzymessupporting
confidence: 78%
“…Biochemically, we show that the deletion of residues 1 to 14 (exon 1) in WT C subunit can introduce instability and can also affect holoenzyme function [49]. Our previous study also indicated that the J-C subunit is less thermostable than WT C subunit [11,12]. Several posttranslational modification sites in the WT C subunit are localized at the other end of the A-helix in exon 1, and these are missing in the fusion protein.…”
Section: Plos Biologymentioning
confidence: 61%
See 1 more Smart Citation
“…Since aberrant kinase activity is known to drive many cancers, we further reasoned that augmented PKA activity could also contribute to the pathobiology of FLC (Druker et al, 2001; Turnham and Scott, 2016). However, one confounding factor is that the pathological DNAJ-PKAc fusion and its native kinase counterpart share similar sensitivities to the inhibitor PKI and efficiently bind R subunits to form type I and type II PKA holoenzymes (Cao et al, 2019; Cheung et al, 2015; Riggle et al, 2016a; Scott et al, 1985). Although physiochemically similar, notable differences between the PKA holoenzyme subtypes include lack of an autoregulatory phosphorylation site in RI isoforms, different in vitro binding affinities for cAMP and dispersal to distinct subcellular sites via interaction with distinct AKAPs (Aggarwal et al, 2019; Burgers et al, 2012; Feramisco et al, 1980; Means et al, 2011; Smith et al, 2018; Taylor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The allosteric networks we describe here may be amplified in the PKA hetero-tetramer composed of two regulatory and two catalytic subunits, where the potential cross-talk between PKA subunits is expanded 12,34,40 . Structural studies of the PKA hetero-tetramer formed with RI isoforms showed the N3A motif of one regulatory subunit stacked against the N3A motif of the neighboring one, forming a helical bundle with several hydrophobic interactions 41,42 . Therefore, it is possible that the dynamic switching response of the N3A motif described here may play additional allosteric regulatory roles by communicating the two regulatory subunits in the PKA hetero-tetramer via quaternary interactions.…”
Section: Discussionmentioning
confidence: 99%